(untitled) (REMUNOM, 2023)
This article seeks to discuss about succession in the context of adoption, specifically about the succession law of de facto adoption. It is known that, for adopted or biological children, there is no distinction in terms of rights and duties. However, adoption must follow legal criteria to be valid. In this sense, Brazil is a country where there is still a lot of actual adoption, that is, adoptions that do not follow the legal criteria. To the detriment, several clashes arise, especially with regard to succession. In short, to deal with the succession in the de facto adoption, it is necessary to be based on the real law, that is, to analyze the factual situation and eliminate conflicts of interest.